2002
DOI: 10.1002/hbm.10058
|View full text |Cite
|
Sign up to set email alerts
|

Comparing brain activation associated with isolated upper and lower limb movement across corresponding joints

Abstract: It was shown recently that functional activation across brain motor areas during locomotion and foot movements are similar but differ substantially from activation related to upper extremity movement (Miyai [2001]: Neuroimage 14:1186-1192). The activation pattern may be a function of the behavioral context of the movement rather than of its mechanical properties. We compare motor system activation patterns associated with isolated single-joint movement of corresponding joints in arm and leg carried out in equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
130
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 54 publications
11
130
2
2
Order By: Relevance
“…Here, the authors demonstrate hand movement observation evoked activity of the rostral ventral premotor cortex, while foot movement observation evoked activity of dorsal area 6, which is in closer proximity to mesial areas. fMRI studies have shown similar patterns of distinction between knee and elbow movements (Luft et al 2002). Detailed analysis has also revealed similar premotor mapping in primates (Rizzolatti et al 1998).…”
Section: Discussionmentioning
confidence: 84%
“…Here, the authors demonstrate hand movement observation evoked activity of the rostral ventral premotor cortex, while foot movement observation evoked activity of dorsal area 6, which is in closer proximity to mesial areas. fMRI studies have shown similar patterns of distinction between knee and elbow movements (Luft et al 2002). Detailed analysis has also revealed similar premotor mapping in primates (Rizzolatti et al 1998).…”
Section: Discussionmentioning
confidence: 84%
“…First, patients with stroke may have difficulty performing isolated joint movements without any associated movements or spasticity, which then may cause larger head motion during MR imaging. 44,49 Second, the BOLD signals in ipsilesional M1 may be significantly decreased or even absent while patients with stroke perform movements with the affected upper or lower extremity. [50][51][52][53] Movement-related BOLD signals may shift from the primary motor cortex to secondary association motor networks or even the contralesional hemisphere in response to stroke lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral activity has been assessed while subjects imagine walking, but the cerebral resources used by an individual to visualize ambulation are open to wide variations across subjects. Prior studies have used toe, foot, or knee movements during fMRI (Debaere et al, 2001;Kollias et al, 2001;Lafleur et al, 2002;Leherricy et al, 1998;Lotze et al, 2000Lotze et al, , 2003bLuft et al, 2002;Sabbah et al, 2002;Sahyoun et al, 2004) and PET (Johannsen et al, 2001;Roelcke et al, 1997) to investigate motor control and somatotopy in normal and neurologically impaired subjects. We have been evaluating ankle dorsiflexion as a potential marker for gains in motor control of the lower extremity during rehabilitation and as a substitute for multijoint walking movements of the affected leg in patients with stroke and SCI (Dobkin, 2000;Dobkin and Sullivan, 2001;Dobkin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%